Proceedings of the 2009 ACM Symposium on Applied Computing 2009
DOI: 10.1145/1529282.1529308
|View full text |Cite
|
Sign up to set email alerts
|

Using web accessibility patterns for web application development

Abstract: Design of accessible Web applications is a complex challenge. The presented concept demonstrates the potential of model-based and user-centered development. Based on Web accessibility patterns, a suitable solution is discussed which can be used to simplify the development process. Using an established approach from Web engineering, the use of patterns is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…However, when CFC value was lower, UML AD outperformed BPMN. [38,39] Different domains that make arguments why they used a specific notation for their work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when CFC value was lower, UML AD outperformed BPMN. [38,39] Different domains that make arguments why they used a specific notation for their work.…”
Section: Discussionmentioning
confidence: 99%
“…The same was stated in different research, performed by Jeschke et al, which claimed that BPMN is wider spread and more intuitive than UML AD. However, it was concluded that BPMN and UML AD are both equally powerful [39].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In another work, Jeschke et al [12] present the integration of web accessibility patterns in the UWE -UML-based Web Engineering. UWE is a Model-Driven Web Development approach which extends the MOF -Meta Object Facility with an appropriate profile for web engineering.…”
Section: Related Workmentioning
confidence: 99%
“…O trabalho de Jeschke et al (2009) demonstra o uso de práticas de desenvolvimento centradas no usuário e baseadas em modelo com o objetivo simplificar o processo de desenvolvimento de aplicações Web acessíveis [30]. Velasco et al (2008) desenvolveram um framework com o objetivo de suprir deficiências de sistemas de avaliação de acessibilidade tradicionais e ao mesmo tempo suportar conceitos mais amplos de Web Compliance aplicados a RIA.…”
Section: Considerações Finaisunclassified